2013
DOI: 10.1063/1.4803530
|View full text |Cite
|
Sign up to set email alerts
|

Applications of high throughput (combinatorial) methodologies to electronic, magnetic, optical, and energy-related materials

Abstract: High throughput (combinatorial) materials science methodology is a relatively new research paradigm that offers the promise of rapid and efficient materials screening, optimization, and discovery. The paradigm started in the pharmaceutical industry but was rapidly adopted to accelerate materials research in a wide variety of areas. High throughput experiments are characterized by synthesis of a "library" sample that contains the materials variation of interest (typically composition), and rapid and localized m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
189
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(196 citation statements)
references
References 414 publications
(447 reference statements)
1
189
0
3
Order By: Relevance
“…In cases where such a "friendly" surface is instead colonized by bacteria, however, the tissue cells quickly become outnumbered and the immune system is faced with a very challenging task. This "race for the surface", first conceptualized by Gristina [7,8,31], often determines the fate of an implant. There is consequently a need for functional biomaterial surfaces that can mediate tissue cell response but also impede bacterial colonization and biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases where such a "friendly" surface is instead colonized by bacteria, however, the tissue cells quickly become outnumbered and the immune system is faced with a very challenging task. This "race for the surface", first conceptualized by Gristina [7,8,31], often determines the fate of an implant. There is consequently a need for functional biomaterial surfaces that can mediate tissue cell response but also impede bacterial colonization and biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…In biomaterials research, the technique has been increasingly applied through automated fabrication of polymeric microarrays for specific cell response evaluation, as well as screening of synthetic substrates for stem cell culture [5,6]. For combinatorial thin films with inorganic composition-gradients, however, most research and development has been focused on materials for electronic, optical, magnetic and energy-related applications [7,8], and corresponding investigations for biomaterials applications are scarce. Although thin film coatings for biomedical implants and devices are all the while being widely researched to improve functionality and safety, no simple solution exists to, for instance, combat or prevent implant-associated infection [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Advances in HTE methodologies have been successfully demonstrated in every class of technologically important materials, and it has been demonstrated that HTE can lead to the discovery and deployment of new materials at unprecedented speed and low cost. 4,5,7,9,[11][12][13][14][15] However, according to the results of a recent HTE workshop, 16 full realization of the MGI vision will require the integration of experiment, computation, and theory, open access to high quality digital data and materials informatics tools, and an educated workforce. This paper reviews the opportunities and challenges facing the use of HTE for materials innovation.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial materials research and development efforts for these applications are underway with combinatorial materials science efforts playing an important role in the discovery of new materials. 1 Optical characterization, particularly in the visible and near-infrared (NIR) regions, is important for evaluating material performance for these and other applications. In combinatorial experiments, the maximum requisite characterization throughput is that of the material synthesis technique.…”
Section: Introductionmentioning
confidence: 99%